2008
DOI: 10.1186/1750-1326-3-11
|View full text |Cite
|
Sign up to set email alerts
|

Prion protein lacks robust cytoprotective activity in cultured cells

Abstract: Background: The physiological function of the cellular prion protein (PrP C ) remains unknown. However, PrP C has been reported to possess a cytoprotective activity that prevents death of neurons and other cells after a toxic stimulus. To explore this effect further, we attempted to reproduce several of the assays in which a protective activity of PrP had been previously demonstrated in mammalian cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 64 publications
3
10
0
Order By: Relevance
“…However, we were unable to detect a significant anti-apoptotic effect of PrP-WT expression under the condition of serum deprivation in Zpl2-1 cells. 3 These results are in line with a former report where no robust cytoprotective effect of PrP was found in the various models tested (45). Because Zpl2-1 cells repeatedly lost the expression of the transgenes during our work, thwarting progress, we used the SH-SY5Y cells for further studies.…”
Section: Resultssupporting
confidence: 90%
“…However, we were unable to detect a significant anti-apoptotic effect of PrP-WT expression under the condition of serum deprivation in Zpl2-1 cells. 3 These results are in line with a former report where no robust cytoprotective effect of PrP was found in the various models tested (45). Because Zpl2-1 cells repeatedly lost the expression of the transgenes during our work, thwarting progress, we used the SH-SY5Y cells for further studies.…”
Section: Resultssupporting
confidence: 90%
“…12 Overall, PrPC may be involved in the neuroprotective and neurotoxic functions, but the effects remain unclear. 13 …”
Section: Introductionmentioning
confidence: 99%
“…Although different cell types used in different studies may explain the observed differences our results are in line with a report where no robust cytoprotective effect of PrP was found in a similar cell culture model (96). While in our model WT PrP offered no protection, we found that the presence of PrPCR increased the sensitivity of the cells to serum deprivation.…”
Section: Effects Of Wt and Cr Prp On Serum Deprivation Caused Cell Dsupporting
confidence: 91%
“…Even though the expression of these mutants causes severe toxicity in PrP null transgenic mice (33)(34)(35) and in CGN cultures (64,97), they show reduced effect (43,98), or no effect (42,96) when expressed in immortalized cell lines. The most obvious phenotype associated with the Shmerling or CR mutations in PrP-s in cell models is the drug hypersensitivity and the occurrence of spontaneous inward cationic currents (37,39).…”
Section: Shadoo and Prpcr Cause Drug Hypersensitivity By A Similar Mmentioning
confidence: 99%